Saúde mental e educação: um estudo sobre depressão infantil com estudantes em atendimento no centro de Atenção Psicossocial Infanto Juvenil (CAPS I) no Município de Bragança/PA - SILVA, Nirvane Linara Sousa da (2024)
This writing is the result of an exploratory study developed in the second half of the year 2023, addressing an analysis of the emotional and mental condition of children in Basic Education of Early Childhood and Elementary Education I based on care at the Psychosocial Care Center for Children and Youth - CAPS I, in the Municipality of Bragança/PA. As a methodological procedure, qualitative and quantitative research was obtained, adding information of an empirical nature to the analysis of numerical data and subjective information and, subsequently, field research, through a survey of the medical records of children/patients welcomed by CAPS I. examining the medical records, we found five cases of children being monitored, distributed between both sexes, aged between six and nine years old, with primary school education in the initial grades. The results showed a high rate of depression symptoms in females, which contradicts recent studies that say that in childhood, boys are more affected.